2015
DOI: 10.1017/s1368980015001007
|View full text |Cite
|
Sign up to set email alerts
|

Gender-specific association of weight perception and appearance satisfaction with slimming attempts and eating patterns in a sample of young Norwegian adolescents

Abstract: Objective: To examine gender-specific associations of weight perception and appearance satisfaction with slimming attempts and eating patterns among young Norwegian adolescents. Design: Cross-sectional study. Adolescent dietary data were reported by parents using a retrospective FFQ. Eating patterns were identified using principal component analysis. Adolescents' reported weight perception, appearance satisfaction and slimming attempts were analysed using cross-tabulation and Pearson's χ 2 test. Associations b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
38
1
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(49 citation statements)
references
References 61 publications
5
38
1
5
Order By: Relevance
“…28 This may be because of differences in body perception in females compared with males leading to stronger motivation to participate in therapeutic interventions, whether surgical or behavioral. 29 In the present study, higher degree of obesity at baseline was protective from poor response to treatment. This is in line with a study by Maggio et al 22 showed that the children with more severe degree of obesity had a larger decrease in BMI Z-score.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…28 This may be because of differences in body perception in females compared with males leading to stronger motivation to participate in therapeutic interventions, whether surgical or behavioral. 29 In the present study, higher degree of obesity at baseline was protective from poor response to treatment. This is in line with a study by Maggio et al 22 showed that the children with more severe degree of obesity had a larger decrease in BMI Z-score.…”
Section: Discussionsupporting
confidence: 47%
“…It is well established that among adult and adolescent candidates of bariatric surgery, females outnumber males in disproportion to their relatively similar rates of obesity . This may be because of differences in body perception in females compared with males leading to stronger motivation to participate in therapeutic interventions, whether surgical or behavioral …”
Section: Discussionmentioning
confidence: 99%
“…Previous research [18,44] confirmed that body satisfaction mattered, being a predictor of dieting and other types of weight control behaviors or binge eating. However, no studies tested if body satisfaction predicts healthy or unhealthy eating behaviors, which in turn predicts unfavorable changes in BMI.…”
Section: Discussionmentioning
confidence: 89%
“…The studies were published between 2005 and 2017. The eligible studies included 39 cross-sectional studies (Al Sabbah et al, 2010;Alwan, Viswanathan, Williams, Paccaud, & Bovet, 2010;Bahreynian et al, 2015;Barker & Galambos, 2007;Bilali, Galanis, Velonakis, & Katostaras, 2010;Canpolat, Orsel, Akdemir, & Ozbay, 2005;Cheung, Ip, Lam, & Bibby, 2007;Claro, Santos, & Oliveira-Campos, 2014;Cook, MacPherson, & Langille, 2007;de Sousa Fortes, Cipriani, & Ferreira, 2013;Deschamps, Salanave, Chan-Chee, Vernay, & Castetbon, 2015;Duncan, Duncan, & Schofield, 2011;Epperson et al, 2014;Fan & Jin, 2015;Guarino et al, 2005;Hayes & Napolitano, 2012;Ibrahim, El-Kamary, Bailey, & St George, 2014;Kachi, 2010;Kim & Kim, 2005;Lee, Ha, Vann, & Choi, 2009;Markey & Markey, 2005;Mase, Miyawaki, Ohara, & Nakamura, 2015;Mustapic, Marcinko, & Vargek, 2015;Oellingrath, Hestetun, & Svendsen, 2016;Quick et al, 2014;Ramberan, Austin, & Nichols, 2006;Roy & Gauvin, 2013;Shamaley-Kornatz, Smith, & Tomaka, 2007;Shi, Lien, Kumar, & Holmboe-Ottesen, 2007;Sirang et al, 2013;Som & Mukhopadhyay, 2015;Tanenbaum et al, 2016;Thomas, Khan, & Abdulrahman, 2010;Ursoniu, Putnoky, & Vlaicu, 2011;…”
Section: Resultsmentioning
confidence: 99%
“…Markey, 2005;Shamaley-Kornatz et al, 2007;Wang et al, 2009;Wharton et al, 2008;Yang et al, 2014;Zullig et al, 2006). Nine studies were conducted in Asia in Hong Kong, Japan, Korea, China, Pakistan, and India (Cheung et al, 2007;Kachi, 2010;Kim & Kim, 2005;Lee et al, 2009;Mase et al, 2015;Shi et al, 2007;Sirang et al, 2013;Som & Mukhopadhyay, 2015;Tanenbaum et al, 2016); eight studies were conducted in Europe in Greece, Spain, Italy, Poland, Croatia, Romani, Norway, and France (Bilali et al, 2010;Deschamps et al, 2015;Espinoza et al, 2010;Guarino et al, 2005;Jaworowska & Bazylak, 2009;Mustapic et al, 2015;Oellingrath et al, 2016;Ursoniu et al, 2011); three studies were conducted in the Middle East in Palestine, Iran, and United Arab Emirates (Al Sabbah et al, 2010;Bahreynian et al, 2015;Thomas et al, 2010); three studies were conducted in Canada (Barker & Galambos, 2007;Cook et al, 2007;Roy & Gauvin, 2013) and South America, in Brazil (Claro et al, 2014;de Santana et al, 2016;de Sousa Fortes et al, 2013); and one each in Australia (Donovan et al, 2006), New Zealand (Duncan et al, 2011), Trinidad and Tobago (Ramberan et al, 2006), Turkey (Canpolat et al, 2005) and the Seychelles…”
Section: Resultsmentioning
confidence: 99%